The in vitro direct mycobacterial growth inhibition assay (MGIA) for the early evaluation of TB vaccine candidates and assessment of protective immunity: a protocol for non-human primate cells - Tanner, R; Hoogkamer, E; Bitencourt, J; White, A; Boot, C; Sombroek, CC; Harris, SA; O'Shea, MK; Wright, D; Wittenberg, R; Sarfas, C; Satti, I; et al. (F1000Research, 2021)
The only currently available approach to early efficacy testing of tuberculosis (TB) vaccine candidates is in vivo preclinical challenge models. These typically include mice, guinea pigs and non-human primates (NHPs), which must be exposed to virulent M.tb in a ‘challenge’ experiment following vaccination in order to evaluate protective efficacy. This procedure results in disease development and is classified as ‘Moderate’ in severity under EU legislation and UK ASPA licensure. Furthermore, experiments are relatively long and animals must be maintained in high containment level facilities, making them relatively costly. We describe an in vitro protocol for the direct mycobacterial growth inhibition assay (MGIA) for use in the macaque model of TB vaccine development with the aim of overcoming some of these limitations. Importantly, using an in vitro assay in place of in vivo M.tb challenge represents a significant refinement to the existing procedure for early vaccine efficacy testing. Peripheral blood mononuclear cell and autologous serum samples collected from vaccinated and unvaccinated control animals are co-cultured with mycobacteria in a 48-well plate format for 96 hours. Adherent monocytes are then lysed to release intracellular mycobacteria which is quantified using the BACTEC MGIT system and colony-forming units determined relative to an inoculum control and stock standard curve. We discuss related optimisation and characterisation experiments, and review evidence that the direct NHP MGIA provides a biologically relevant model of vaccine-induced protection. The potential end-users of the NHP MGIA are academic and industry organisations that conduct the assessment of TB vaccine candidates and associated protective immunity using the NHP model. This approach aims to provide a method for high-throughput down-selection of vaccine candidates going forward to in vivo efficacy testing, thus expediting the development of a more efficacious TB vaccine and offering potential refinement and reduction to the use of NHPs for this purpose.